Use of electroencephalography (EEG) for comparing study of the external space perception of traditional and modern commercial districts. Issue 6 (2nd November 2021) - Sun, Xia; Li, Zao
ABSTRACT: With the acceleration in globalization, cities have tended to become similar, and commercial districts have gradually lost their local characteristics. Hence, utilizing scientific means to assess human perceptions of traditional and modern districts in an objective manner, this study applies the electroencephalography (EEG) test and the Semantic Differential (SD) method to evaluate the external space perceptions of traditional and modern commercial districts. The results show that the alpha wave mean value of traditional samples is greater than that of modern samples among all electrodes, and most electrodes demonstrate a significant difference. Meanwhile, the alpha wave energy value of a single electrode of different subjects is mostly larger in the traditional samples, meaning that traditional districts can lead to an increase in the brain's alpha waves. In addition, the SD results show that traditional samples make people feel more comfortable and relaxed; regarding the cultural atmosphere, they are more abundant in detail and distinct; regarding open and closed spaces, they are more closed and covert. The results also show that the electroencephalography (EEG) test can be applied to an evaluation of environmental perception to boost sustainable development of traditional commercial districts and offer more possibilities for future design.